DEFENSIVE CAPABILITIES OF THE KHOREZM CITIES OF THE TIMURID ERA (Scientific journal of the Fergana State University, 2024)
The article analyzes the defense capabilities of Amir Temur and the cities of Khorezm during the Timurid era based on historical sources. Based on the description of the military operations in the interpretation of the political processes that occurred during the Timurid period, the condition of the defense structures of the Khorezm cities was researched and preliminary scientific conclusions were given. City gates, defensive walls and ditches, their importance in the battle process are shown on the example of Khorezm cities.